please do answe this question urgent please
Attachments:
![](https://hi-static.z-dn.net/files/d2c/b3d26b07c14a5cbce8082faa65b86bf2.jpg)
Answers
Answered by
0
0
Step-by-step explanation:
please thank my answer and follow me mark me as brainlist answer
Attachments:
![](https://hi-static.z-dn.net/files/d2a/2a2241189cd2aa6a4de519228aad7d31.jpg)
Answered by
0
Answer:
HOPE IT WILL HELP YOU
Step-by-step explanation:
let a2−b2=x1;b2−c2=y1;c2−a2=z1
x1+y1+z1=0
⇒x13+y13+z13=3x1y1z1=3(a2−b2)(b2−c2)(c2−a2)
let a−b=x2;b−c=y2;c−a=z2
x2+y2+z2=0
⇒x23+y23+z23=3x2y2z2=3(a−b)(b−c)(c−a)
So,
x23+y23+z23x13+y13+z13=(a+b)(b+c)(c+a)
THIS IS YOUR ANSWER OKAY
Similar questions
Physics,
3 months ago
Hindi,
3 months ago
Social Sciences,
3 months ago
History,
8 months ago
Math,
8 months ago